UPAYA PEMERINTAH DAERAH PROVINSI RIAU DALAM MEMPERSIAPKAN KELEMBAGAAN REDUCTION OF EMISSION FROM DEFORESTATION AND FOREST DEGRADATION (REDD) TAHUN 2012 - Oktaviana, Putri Azhari; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The research is entitled “The Effort of Riau Province Government in preparing Reduction of Emissions from Deforestation and Forest Degradation (REDD) intuition in 2012”. This research is motivated by Riau Province which is one of the nine forest territory in Indonesia are set by the government as a provincial of REDD implementation. Riau province with the ample forests and the largest peat lands in Sumatra as well as the largest contributor to CO2 emissions in Indonesia. Along with designee of Riau Province as a pilot province, Riau Governor has established the task Force of REDD provincial whose job is to prepare future at the provincial level .The aim of this research is to determine the local government's efforts in preparing the REDD institution in 2012 and also to identify factors inhibiting Riau province government’ efforts in preparing for REDD institution in 2012.The results of this research showed the efforts done by Riau province government in preparing the REDD institution, first in the early stages through the Governor's decision No. 26 of 2008 on Climate Change Information Center Riau province, from Department of Forestry and Estate Crops itself formed a working group reducing emissions from deforestation and degradation (REDD) in order to handling the climate change in the Riau Province. Next the designee of technical team members of mitigation and adaptation planners of climate change and the designee of central team of Riau Province climate change which is a follow up of the Governor's decision No. 26 of 2008 on Climate Change Center of Riau Province. Subsequent attempts by the government of Riau province, namely the establishment of the REDD Task Force where REDD task force is forming a team of writers to create documents of Provincial Strategy Action Plan ( SRAP ) which are as guidelines to guarantee consistency in the effort to reduce carbon emissions and provide direction for the development of local governments to carry out various activities mitigation that directly and indirectly reduce carbon emissions by a certain time.Key Words : REDD, Local Government efforts, Riau Province